The competitiveness of municipal elections in the Perm region, held on a single day of voting 9 september 2018 - Kovin, V.S.; Petrova, R.I. (Perm Federal Research Centre Journal, 2018)
The article analyzes the competitiveness of municipal election campaigns that took place on a single voting day on September 9, 2018 in the Perm region. Using the method of calculating the effective number of candidates, a competitiveness rating of the municipal elections of deputies of representative bodies of government was built. The study showed that most of the municipal election campaigns belong to non-competitive elections (20 out of 26), and only six campaigns can be classified as poorly competitive. A decrease in competitiveness is also observed in the territories of the region united in single municipal units.